Genomic insights into renal diseases: advancements and implications - Nicholas Aderinto; Gbolahan Olatunji; Emmanuel Kokori; Ikponmwosa Jude Ogieuhi; Adetola Emmanuel Babalola; Komolafe Babajide Ayodeji; Muhammadul-Awwal Irodatullah Bisola; Ajekiigbe Victor Oluwatomiwa; Ibukunoluwa V. Ishola (SpringerOpen, 2024)
Abstract Renal diseases pose significant challenges to global health. With conditions like chronic kidney disease (CKD) on the rise, there is an urgent need for deeper insights into their underlying mechanisms and risk factors to improve patient outcomes. Genomic research has emerged as a powerful tool in unraveling the complex genetic architecture of renal diseases, offering opportunities for personalized medicine, early diagnosis, and targeted therapies. This paper provides an overview of recent advancements in genomic research related to renal diseases and their implications for clinical practice. Through genomic analyses such as genomic-wide association studies (GWAS), whole exome sequencing (WES), and functional genomics, researchers have identified numerous genetic variants, metabolic pathways, and molecular mechanisms contributing to different kidney diseases. Furthermore, through functional genomic approaches and polygenic risk scores (PRS), studies have made significant strides in predicting disease risk and stratifying high-risk individuals for early intervention. The integration of genomic insights into clinical practice enables more accurate risk assessment and tailored treatment strategies, although challenges such as genetic heterogeneity and population-specific variations remain. The search for effective biomarkers in nephrology has gained momentum in recent years, driven by the limitations of traditional markers like serum creatinine and the need for more precise diagnostic and prognostic tools. Despite significant progress, challenges remain in translating these findings into clinical practice, including the need for cost-effective validation methods and the integration of genomic data into routine patient care.